Honduras : Technical Assistance Report-Fiscal Transparency Evaluation. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2021)
This report evaluates Honduras's fiscal transparency practices in relation to the IMF Fiscal Transparency Code (FTC). Honduras's score is similar to those of other Latin American countries and emerging market economies that have undergone the evaluation. In relation to the fiscal transparency principles, Honduran practices are considered basic in 15 areas; good in seven areas; and advanced in six areas. Fiscal transparency practices in the area of fiscal forecasting and budgeting are the strongest, while the fiscal risk analysis and management practices are the weakest. Finally, Honduras's current fiscal transparency practices fall short of the FTC principles in eight areas.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Honduras